2006
DOI: 10.1259/bjr/69395941
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound spectrum in intraductal papillary neoplasms of breast

Abstract: Intraductal papillary neoplasms (IPNs) of breast form a wide spectrum of pathological changes with benign intraductal papilloma occupying one end of the spectrum and papillary carcinoma at the other end. Intraductal papillomas are known to occur anywhere within the ductal system and are broadly classified into central and peripheral types. Intraductal papillary carcinoma is an uncommon ductal malignancy forming papillary structures, and these lesions characteristically lack the myoepithelial layer present in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 6 publications
5
74
0
11
Order By: Relevance
“…8 They observed that intraductal papillary neoplasms (IPNs) of breast form a wide spectrum from benign intraductal papilloma to papillary carcinoma and are broadly classified into central and peripheral types.…”
Section: Discussionmentioning
confidence: 99%
“…8 They observed that intraductal papillary neoplasms (IPNs) of breast form a wide spectrum from benign intraductal papilloma to papillary carcinoma and are broadly classified into central and peripheral types.…”
Section: Discussionmentioning
confidence: 99%
“…However, these tumors are not always visible on standard mammograms. Sonographically, they are associated with three basic patterns: that of an intraductal mass, with or without duct dilatation; that of an intracystic mass; and that of a predominantly solid formation that occupies virtually all of the duct [1]. Color and power Doppler imaging reveal abundant vascularization with branches arising from a central pedicle [6].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of these tumors is 2e3%; they develop in women between the ages of 30 and 77 years [1]. Two types of intraductal papillomas are generally distinguished: central and peripheral.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of dilatation of ducts associated with a mass is a good indicator for a papilloma [11], and a useful sign for differentiating intraductal papillary lesions from other benign lesions, such as fibroadenoma and fibrocystic diseases [12]. ABVS coronal view is a satisfactory plane for most breast papillary neoplasms because it could demonstrate duct dilation more frequently (Figures 2-4).…”
Section: Ultrasound Features On Automatic Breast Volume Scan Solitarymentioning
confidence: 99%